Congenital afibrinogenemia in a 4-year-old girl complicated with acute lymphoblastic leukemia - Özcan, Alper; Samur, Bahadır; Akyol, Şefika; Erdoğmuş, Necdet Arda; Patıroğlu, Türkan; Karakükçü, Musa; Ünal, Ekrem (The Turkish Journal of Pediatrics, 2020)
Background. Congenital fibrinogen deficiency is one of the rare inherited coagulation disorders. Congenital fibrinogen deficiency complicated with a hematological malignancy can be life threatening. Case. We present a four-year-old girl with congenital fibrinogen deficiency complicated with acute lymphoblastic leukemia. Conclusion. This case aims to highlight therapeutic approaches for the management of afibrinogenemia patients with acute leukemia.